NOVEL TANAH SURGA MERAH BY ARAFAT NUR (2017): BETWEEN SACRIFICE AND BETRAYAL - Nurul yana, Nurul yana; Iswadi, Iswadi (Journal of English Education and Social Science, 2023)
The title of this research is Novel Tanah Surga Merah By Arafat Nur (2017): Between Sacrifice and Betrayal. The purpose of this research is 1) To analyze and describe how the main character’s conflicts between sacrifice and betrayal, 2) To know the moral values in the novel Tanah Surga Merah, and 3) To know the religious values in the novel Tanah Surga Merah. The method utilized in this research is library research design. In collecting research data results, the researcher conducted primary data and secondary data. The primary data of this research was a novel by Arafat Nur entitled Tanah Surga Merah. To obtain the results from the primary data, the researcher focused on the point of sacrifice and betrayal, then focused on the values of this novel. Meanwhile, the research outcome from the secondary data in this research was obtained from reading the books, internets, articles, or other documents related to the novel Tanah Surga Merah by Arafat Nur. In analyzing the data results, the researcher adopted the technique form Miles & Huberman (1994) that consisted of data reduction, data display, and data verification. The extent of the sacrifice made by the main character and the betrayal committed by him for the path of morality and equity and how it is greatly portrayed in the novel's plot about the circumstances of the Acehnese society that have changed substantially in terms of moral values and religious values was discovered as a result of analyzing the Tanah Surga Merah novel.